A sea of islands: How a regional group of Pacific states is working to achieve SDG 14 - Meg Taylor (UN Chronicle, 2017)
The health of our oceans is fundamental to the health of our planet. Ninety-eight per cent of the area occupied by Pacific Island countries and territories is ocean. We sometimes refer to ourselves as Big Ocean Stewardship States in recognition of this geography. The Pacific Ocean is at the heart of our cultures and we depend on it for food, income, employment, transport and economic development